AS REGIÕES NATURAIS DE PERNAMBUCO, O MEIO E A CIVILIZAÇÃO (RECENSÃO DE UM LIVRO) - Pickel, D. Bento J. (REVISTA DE AGRICULTURA, 2015)
AS REGIÕES NATURAIS  DE PERNAMBUCO, O MEIO E A CIVILIZAÇÃO (RECENSÃO DE UM LIVRO)